The survey of porcine teschoviruses, sapeloviruses and enteroviruses B infecting domestic pigs and wild boars in the Czech Republic between 2005 and 2011 - Prodělalová, Jana (Infection, genetics and evolution, 2012)
This study presents results of epidemiological survey and genetic characterisation of porcine enteric picornaviruses belonging to the genera Teschovirus, Sapelovirus, and Porcine enterovirus B. Faecal or gut content samples from domestic pigs (Sus scrofa f. domestica) and the cecal content of wild boars (Sus scrofa) of different ages (collected between 2005 and 2011) were analysed by molecular methods. Porcine enterovirus B was the most prevalent virus detected in both domestic pigs and wild boars (50.2% and 69.4%, respectively), followed by Porcine teschovirus and Porcine sapelovirus. The majority of positive domestic pigs (69.4%) and wild boars (64.3%) were infected with two or three tested viruses. There was no significant difference in prevalences of teschoviruses, sapeloviruses, and enteroviruses among healthy and diarrhoeic pigs. Results of epidemiological survey demonstrated that all target viral genera are common in Czech farms producing pigs and wild boars. Amplified nucleotide fragments of VP2 region obtained from randomly selected both historical and recent Teschovirus isolates were sequenced. Based on sequence data, historical Porcine teschovirus isolate CAPM V-180, previously determined as serotype 1 was reclassified into serotype 11. Moreover, another recent Porcine teschovirus isolate OH264/2010 was described and classified into serotype 11. Four nontypeable PTV strains (historical isolate CAPM V-182/1976 and recent isolates JA247/2010, NI429/2010, and BR1576/2007) identified in this study might represent novel serotypes. To the best of our knowledge, our study represents the first description of this serotype in the Czech Republic.
Keywords: Serotyping; Molecular Typing; Teschovirus; surveillance populace; pikornavirové infekce; feces; Phylogeny; Sus scrofa; Picornaviridae; prevalence; Cecum; Capsid Proteins; cékum; zvířata; Swine; Feces; fylogeneze; Czech Republic; virové plášťové proteiny; molekulární typizace; enteroviry prasat; Enteroviruses, Porcine; Prevalence; Picornaviridae Infections; Population Surveillance; Animals; Česká republika; prasata; sérotypizace